Teaching-learning evaluation on the ICNP® using virtual learning environment - Carolina Costa Valcanti Avelino; Lívia Cristina Scalon da Costa; Soraia Matilde Marques Buchhorn; Denismar Alves Nogueira; Sueli Leiko Takamatsu Goyatá
ABSTRACT Objective: Evaluating the teaching-learning process of undergraduates and nursing professionals on the International Classification for Nursing Practice (ICNP®) through a course on Moodle Platform. Method: Mixed research conducted with 51 nursing students and nurses. Many technological and educational resources were used. To collect data, two semi-structured questionnaires were applied and focus groups were carried out. Statistical and thematic analysis of the data was performed. Results: There was a correlation between the Wiki variable, the Animation Video (p = 0.002) and the Arch Method (p = 0.04), as well as a correlation between the Forum, the Virtual Book (P < 0.001) and time (p = 0.009). Three topics emerged: innovation in the application of technological resources, distance education in the professional education and permanent education and the teaching-learning process on the ICNP® in a collaborative way. Conclusion: Teaching-learning strategies and technological resources used were pointed out as innovative and helped students have a better performance.